(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Goal: The purpose of this paper is to investigate optimum compression to ventilation ratios in Cardiopulmonary Resuscitation (CPR). Methods: Mathematical modeling approach is used. Equations describing oxygen, carbon dioxide exchange and blood flow as functions of the compression to ventilation ratio during CPR are developed. The model is validated against normal physiology and animal studies of CPR. Then the model equations are solved to find the optimum compression to ventilation ratios for both professional and lay rescuers. As rescuer performance might vary greatly, Monte Carlo simulations with parameters of rescuer performance randomly chosen are performed to examine whether the optimum compression to ventilation ratios achieved above fit most cases. Results: Results show that the optimum compression to ventilation ratio is around 50:2 for professional rescuers, and is round 70:2 for lay rescuers. Conclusion: The 30:2 compression to ventilation ratio, which is specified in International Guideline, might not be optimum for professional rescuers, might be even worse for lay rescuers. It suggests the 50:2 and 70:2 compression to ventilation ratios might be optimum for professional and lay rescuers respectively. Significance: The 50:2 and 70:2 compression to ventilation ratios might maximize optimum oxygen delivery to body tissue during CPR, and thus lead to better survival rates.